(3Yjhf GdCNHGQs - (3GdGTHjdj , CHh eMeO YjSi Hf CMeO Hf Ydj GddNej GdETHjdj, YjSi GddNej,J (B420 (3g` s
(3ChdgG (B:s
(3bGd GdeDda aEfi deG fXQJ ai cJH GdYdeGA CLGHJfi faSi Zdi LeY gPG GdcJGH hSejJg HcJGH Yjhf GdCNHGQ s
(3BNQgG (B:s
(3Je cJGH Yjhf GdGNHGQq s
(3ChdgG agQS HehVhYGJ GdcJGHs
(3HgG fXGe GdJYbjHIs
(3SbWJ efgG GdhQbI GdChdi hGdCNjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B590s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1184s
Keywords: (3GdJUha hGdBOGH GdTQYjIs